Pertanggungjawaban Negara Terhadap Pengingkaran Keadilan dalam Arbritase Internasional - Recca Ayu Hapsari (Law Faculty of Universitas Bandar Lampung, 2016)
Denial of justice as be the emergence of state responsibility in international law if the country does not meet certain standards in carried out justice against foreigners . In essence, the denial of justice is a concept of protection for investors , which is based on three elements , foreigners, the state responsibility under international law , and how unfair in holding the judiciary . The legal consequences of denial of justice is a state should be responsible for either restitution orcompensation . ( Zephaniah B.P. Naidoo , 2015: 11 ) . Denial of justice (denial of justice) this comes as no availability or provides a means of justice as appropriate in resolving the case by using local legal institutions ( the exhaustion of local remedies ) . So when there is denial of justice one party can sue the State Responsibility of the provider country of law .